On the Underestimation of Migration's Income and Poverty Impact - Schiff, Maurice (2012)
In estimating the impact of migration on income and poverty, most existing studies have overlooked the fact that migration changes the size of the household. The 'corrected' impact that accounts for changes in household size is presented analytically and is estimated on the basis of data from nationally representative household surveys in Albania and Ghana. The analysis considers three poverty measures and four groups of migrant households: those with internal, international, internal and international, and internal and/or international migrants. The ratio of the corrected to the uncorrected impact on per capita income for Ghana (Albania) averages from 2.7 to 4.5 (2.5-3.8), and the ratio for the poverty impact averages from 2.6 to 4.4 (2.1-6.4). Thus, abstracting from changes in household size may result in a substantial underestimate of the impact of migration on income and poverty.